The Front Handspring Vault
One of the most exciting and powerful events in gymnastics is the vault. This event requires speed, quickness, and explosive power. The vault begins with a strong, accelerated run, a hurdle to the springboard, the critical takeoff from the board, turn over trom the board to the horse, and finally, repulsion from the horse. The vault is the fastest of the four gymnastics events with all of the components occurring in the time space of only a few seconds. In women's gymnastics, vaults are divided into four categories based on the various body positions and movements performed by the gymnast. The four types are handsprings, forward saltos, backward saltos, and vaults from a roundoff. The basic technical vault is the front handspring. In performing other complex vaults a gymnast will apply the techniques learned in this basic vault. The front handspring vault can be explained by many physics concepts. These include acceleration, energy, and momentum. With an understanding of how these concepts act in the vault, a gymnast can apply them and better her technique.